Obesity-stroke paradox and initial neurological severity. Issue 7 (10th September 2014) - Kim, Yerim; Kim, Chi Kyung; Jung, Seunguk; Yoon, Byung-Woo; Lee, Seung-Hoon
Abstract : Background and purpose: An obesity paradox in patients with stroke has been documented. However, although the initial neurological severity (INS) is generally the most important prognostic factor, the impact of this paradox has not been considered in most previous studies. We sought to investigate the impact of obesity on INS in patients with ischaemic stroke and to investigate whether it is a significant risk factor for short-term outcomes. Methods: A total of 2670 patients from Seoul National University Hospital with ischaemic stroke were enrolled from October 2002 to May 2013. Baseline information, including body mass index (BMI) and INS, was collected at admission. Associations between obesity and INS were analysed. In addition, we evaluated the effect of BMI on modified Rankin Scale (mRS) 3 months after stroke onset. Results: Among the 2670 patients, patients whose BMI levels were higher than the chosen reference level had reduced risks of moderate to severe INS (Q2: OR, 0.65; 95% CI 0.49 to 0.87; Q3: OR, 0.48; 95% CI 0.35 to 0.65; Q4: OR, 0.39; 95% CI 0.28 to 0.54; and Q5: 0.31; 95% CI 0.22 to 0.44). In addition, of the 703 patients with available 3-month mRS patients with higher BMI levels seem to have had more favourable outcomes. Such associations disappeared after adjusting for INS. Conclusions: In our study, although obesity was associated with better short-term functional outcomes, INS might be a more important prognostic factor. Therefore, initial status should also be considered when considering an 'obesity paradox' in chronic diseases.